Advanced research on applied mechanics, mechatronics and intelligent system : selected, peer reviewed papers from the 2013 International Conference on Applied Mechanics, Mechatronics and Intelligent System (AMMIS2013), April 19-21, 2013, Changsha, China - Guojin, Chen (Applied mechanics and materials ;, 2013)
Collection of selected, peer reviewed papers from the 2013 International Conference on Applied Mechanics, Mechatronics and Intelligent System (AMMIS2013), April 19-21, 2013, Changsha, China. The 57 papers are grouped as follows: Chapter 1: Applied Mechanics; Chapter 2: Sensors, Measurement Technologies and Equipment; Chapter 3: Mechatronics and Automation; Chapter 4: Intelligent System and Information Processing Technology.